Corrosion of the galvanizing of galvanized‐steel electricity transmission towers . Issue 8 (1st February 2017) - Rodger, J.; Bartlett, S.; Atrens, A.
Abstract : The remaining galvanizing layer thicknesses were measured on a selection of towers in the local Brisbane area. The galvanized steel members of the electricity transmission towers in the local area have large remaining galvanizing layer thicknesses. The measured local zinc corrosion rate of 0.18 μm per year was small compared to the data scatter of measured galvanizing layer thicknesses, and was consistent with the low expected zinc corrosion rate of 0.1–4 μm per year. The remaining galvanizing layer is expected to last over 20 years. Abstract : The remaining galvanizing layer thicknesses were measured on a selection of towers in the local Brisbane area. The galvanized steel members of the electricity transmission towers in the local area have large remaining galvanizing layer thicknesses. The measured local zinc corrosion rate of 0.18 µm per year was consistent with the low expected zinc corrosion rate of 0.1–4 μm.